Evaluation of effectiveness of self-directed learning in 2nd Professional year medical undergraduates - Samiksha J Sonar; Anuradha M Gandhi; Prakruti Parth Patel; Chetna K Desai (Wolters Kluwer Medknow Publications, 2023)
Introduction: Self-directed learning (SDL) is one of the recommended teaching-learning methods for Indian medical graduates to become a lifelong learner. Methodology: The study was conducted in 2nd year medical undergraduates. A lecture (Cholinergic Transmission and Cholinergic Drugs) was conducted followed by sensitization of students for SDL method and sharing of SDL topic (organophosphate poisoning). After 3 days, in the 1st SDL session, students were sensitized for SDL topic. A pretest (multiple-choice questions [MCQs] of SDL topic) was administered and resource materials were shared at its end. In intersession period, case-based scenarios, trigger words, and videos were shared in a preformed WhatsApp group. During the 2nd session, facilitators facilitated discussion of the topic in small groups of students using case-based scenarios. Posttest (MCQs) for students and feedback for students and facilitators were administered. Results: Data collected from 61 students showed a statistically significant difference between the means of posttest compared to pretest (standard error: 2.45, P < 0.05, confidence interval - 95%). Posttest scores showed that more than 45% of the students answered correctly 80% of questions, compared to pretest. More than 70% of students and facilitators agreed/strongly agreed that SDL makes topic interesting and effective for teaching/learning and leads to better student-teacher interaction. About 70% of students and 55% of facilitators found that SDL method should be implemented for more topics in curriculum. Learning issues faced by 21 students (need for more information resources, time-consuming method, difficulty in remembering dosage schedule, clinically correlating topic, and language barrier during discussion) were solved by students using of other online and offline information sources, revising the topic and discussing with co-learners. Conclusion: SDL was helpful for students in improving knowledge, communication skills, and analyzing case-based scenarios for any given topic.